Упростите выражение:(a-b)^2-a(a+2b)Преобразуйте в многочлен:а) (2x^2-3y^3)^2б)2(a-3)^2
Упростите выражение:
(a-b)^2-a(a+2b)
Преобразуйте в многочлен:
а) (2x^2-3y^3)^2
б)2(a-3)^2
Ответ(ы) на вопрос:
Упростите выражение:
(a - b)² - a(a + 2b) = а² - 2ав +в² - а² - 2ав = в² - 4 ав
Преобразуйте в многочлен:
а) (2x² - 3y³)² = 4х⁴ - 2 * 2x² * 3y³ + 9у⁶ = 4х⁴ - 12x²y³ + 9у⁶
б) 2(a - 3)² = 2(а² - 6а + 9) = 2а² - 12а +18
(a-b)^2-a(a+2b)=a^2-2ab+b^2-a^2-2ab=b^2-4ab
Преобразуйте в многочлен:
а) (2x^2-3y^3)^2=4x^4-12x^2y^3+9y^6
б)2(a-3)^2=2a^2-12a+18
Не нашли ответ?
Похожие вопросы